Gut microbiota composition is associated with disease severity and host immune responses in COVID-19 - Fan, Ruyue; Liu, Shuai; Sun, Na; Yang, Ying; Deng, Xia; Hu, Bin; Sun, Changhua; Wen, Chengli; Li, Hui; Cheng, Dong; Huang, Chuanjun; Hou, Peibin; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Human gut microbiota plays a crucial role in the immune response of the host to respiratory viral infection. But evidence regarding the association between gut microbiome, host immune responses, and disease severity in coronavirus disease 2019 (COVID-19) remains insufficient.To better comprehend the interactions between the host and gut microbiota in COVID-19, we conducted 16S rRNA sequencing and characterized the gut microbiome compositions in stool samples from 40 COVID-19 patients and 33 non-pneumonia controls.And several hematological parameters were assessed to determine the immune status.We found that the gut microbial composition was significantly changed in COVID-19 patients, which was characterized by increased opportunistic pathogens and decreased commensal bacteria. The frequency of prevalent opportunistic pathogens Enterococcus and Lactobacillus increased, especially in severe patients; yet the abundance of butyrate-producing bacteria, Faecalibacterium Roseburia, and Anaerostipes decreased significantly, and Faecalibacterium prausnitzii might help discriminate severe patients from moderate patients and non-pneumonia people. Furthermore, we then obtained a correlation map between the clinical characteristics of COVID-19 and severity-related gut microbiotas. A notable correlation between the abundance of Enterococcus faecium and abnormal neutrophil or lymphocyte percentage was observed in all COVID-19 patients. And Faecalibacterium was positively correlated with lymphocyte counts, while negatively correlated with neutrophil percentage.These results suggested that the gut microbiome could have a potential function in regulating host immune responses and impacting the severity or consequences of diseases.